A novel fluorescence polarization assay for determination of penicillin G in milk. (1st January 2016) - Pennacchio, Anna; Varriale, Antonio; Scala, Andrea; Marzullo, Vincenzo Manuel; Staiano, Maria; D'Auria, Sabato
Highlights: A fluorescence polarization sensing assay is described for the detection of penicillin G in raw milk matrices. The sensitivity of the fluorescence assay is in the nano molar range. The fluorescence assay is fast and allows for a timely detection of penicillin G in milk. Abstract: Detection of penicillin G in milk is of interest because of the wide use of this antibiotic in livestock. Current analytical methods used to quantify the penicillin G in milk are based on HPLC, mass spectrometry and electrophoresis. These methodologies are time-consuming and require trained personnel. In addition, it is not easy to envisage the development of a portable device for in situ analyses based on these methods. We present a novel sensing approach for detecting the presence of penicillin G in milk. The proposed method is based penicillin G conjugate labeled with red-emitting dye with properly produced anti-penicillin G antibodies. The results obtained suggest our method could be applied directly in milk without interference from other substances. The limit of detection of the method was 1.0 nmol/L, which is much less than the required MRL in EU regulations (12.0 nmol/L).